Karakteristik Fisikokimia dan Sensori Permen Jelly Kulit Buah Kopi dengan Penambahan Gelatin dan Sari Lemon - Khalieda Zia; Yuliani Aisyah; Zaidiyah Zaidiyah; Heru Prono Widayat (Jurnal Teknologi dan Industri Pertanian Indonesia, 2019)
In the field of food, coffee waste begins to be developed by processing it as a beverage product. The skin of coffee fruit can also be processed as a food product, one of which is jelly candy. This study aims to study jelly candy making with the addition of gelatin as a gelling agent and the addition of lemon juice to produce coffee fruit skin jelly candy that has physicochemical and sensory characteristics that meet SNI quality requirements. The design used was factorial Completely Randomized Design consisting of 2 (two) factors. Factor I concentration of gelatin (G) and Factor II is the concentration of lemon water (L). Factor I consists of 4 levels, namely G1 = 10%, G2 = 15%, G3 = 20% and G4 = 25%, while factor II consists of 3 levels, namely L1 = 5%, L2 = 10% and L3 = 15%. Each treatment was repeated 2 times to obtain 24 experimental units.The concentration of gelatin and the concentration of lemon have a very significant effect on water content and pH value. The concentration of lemon has a significant effect on the value of hedonic organoleptic taste. Both interactions have a very significant effect on the value of organoleptic hedonic texture. The results of the analysis of coffee fruit peel jelly candy have an average moisture content of 21.25%, 0.95% ash content, pH 4.53, sensory hedonic color (3.50 neutral reception), aroma (3.48 neutral acceptance), taste (3.50 neutral acceptance), texture (3.59 likes reception).The results showed that 10% gelatin concentration and 10% lemon concentration (G1L2) were the best treatments obtained through the ranking test. The jelly candy produced has 21.32% moisture content characteristics, 1.55% ash content, pH 4.71, 14.09% antioxidant activity, 3.03 mg / 100g vitamin C levels, 3.55 sensory colors (likes) , aroma 3.45 (neutral), taste 3.48 (neutral) and texture 3.43 (neutral).